Evidence of Malodorous Chloroanisoles in “Mold Houses” Was Omitted When Indoor Air Research Evolved - Johnny C. Lorentzen; Gunnar Johanson (Microorganisms)
Herein, we address the peculiar lack of scientific reporting on odor potent chloroanisoles (CAs) in the built environment. We have searched and critically examined sources beyond peer-reviewed scientific journals, namely research conferences, parliamentary records, newspaper articles, and cartoons. We provide evidence that CAs evolved on a large scale in Swedish buildings in the early 1970s and evoked a typical sticky malodor that was attributed to mold and gave rise to the term “mold houses”. The term first appeared in Swedish newspapers in 1978, and the media attention increased rapidly. The malodorous “mold houses” reached the Swedish parliament and led to economic compensation for afflicted homeowners. The “mold houses” became “sick houses” as researchers, predominantly from Sweden, introduced and became world leaders on the “sick buildings syndrome” (SBS). Researchers became aware of the CAs but did not mention them in peer-reviewed articles, just as they did not mention a well-known source of the sticky malodor, namely, legacy preserved wood where CAs were formed through microbial methylation of toxic chlorophenols (CPs). Thus, the mold story from the early 1970s was maintained and prevented the malodorous CAs from becoming recognized as indicators of the presence of hazardous CPs. Our study is the first to report the impact of an indoor malodor, not only on a few people, but on society.